Short Term Load Forecasting Using Type-II Fuzzy Logic Systems - Sharma, Sharad (My University, 2014)
The main objective of short term load forecasting (STLF) is to provide load predictions for generation scheduling, economic load dispatch and security assessment at any time. This dissertation presents a solution methodology using Type-1 Fuzzy Logic approach and Type-2 Fuzzy Logic approach for short term load forecasting and is implemented on historical data that includes temperature, humidity, wind speed and load data for forecasting the load. The proposed Type-2 Fuzzy Logic approach has been implemented on weather sensitive data and the accuracy of the results has been compared with Type-1 Fuzzy Logic approach. Jaipur Vidyut Nigam hourly load data is collected from State Load Dispatch and Communication Centre, Rajasthan Vidyut Parasaran Nigam. The results are obtained from two different approaches are compared and the accuracy of Type-2 Fuzzy Logic approach is reported as better.
ME, EIED
Keywords: Load forecasting; type-I; fuzzy logic; type-II; weather; type reduction